Risk stratification of ulcer-like projection in uncomplicated acute type B aortic intramural haematoma. (15th July 2021) - Chen, Lyufan; Yang, Fan; Liu, Jitao; Luo, Songyuan; Yuan, Hui; Fan, Ruixin; Zeng, Hongke; Geng, Qingshan; Luo, Jianfang
Abstract:  : OBJECTIVES: This study aimed to investigate the morphological evolution and risk stratification of ulcer-like projection (ULP) in patients with uncomplicated acute type B aortic intramural haematoma. METHODS: A retrospective study was conducted on patients with uncomplicated acute type B intramural haematoma admitted in our institution from January 2015 to June 2020. The primary end points were adverse aortic events (AAE), including aortic rupture, aortic dissection, aortic aneurysm and ULP enlargement. RESULTS: The study cohort comprised 140 patients, including 62 (44%) and 78 (56%) patients with and without initial ULP, respectively. AAE occurred in 13 patients (9%) in the early term and 42 patients (33%) in the mid-term. Compared with patients without ULP, patients with initial ULP had no significant difference in early outcomes but a higher mid-term AAE rate [8% vs 11%, odds ratio (OR) 1.5, P  =   0.47; 17% vs 55%, OR 6.0, P  <   0.001]. Significantly higher AAE rate was observed in patients with high-risk ULP (depth ≥5.0 mm and located in the proximal aortic segments) than those with only low-risk ULP (depth <5.0 mm and/or located in the distal aortic segments) (87% vs 51%, OR 6.2, P  =   0.014). In the multivariable analysis, high-risk ULP was an independent predictor of AAE (hazard ratio 2.8, P  =   0.009). CONCLUSIONS: High-risk ULP is a rapidly evolving entity and a marker of AAE despite optimal medical therapy. Therefore, close follow-up and prompt intervention are recommended for patients with high-risk ULP.